Individual psychology as component of entrepreneurial Process: The Cognitive Perspective Contribution of the New Venture Creation among E-Commerce Entrepreneurs in Malaysia - Ahmad Firdause Md Fadzil; Mohd Rafi Yaacob; Mohd Nazri Muhayiddin (2017)
: Studies on entrepreneurs as one of the main components contributing to entrepreneurship particularly for new venture creation processes, has been widely highlighted by previous researchers. An entrepreneur is the main actor in entrepreneurship based on how they think and make decisions. Most previous researchers studying the cognitive aspects of the entrepreneur have looked at the process of creating new ventures in general, but research focusing on creating e-commerce businesses has not been investigated much at all. The aim of this study is to identify how the role of cognitive characteristics of e-commerce entrepreneurs has contributed to the creation of new e-commerce businesses in Malaysia. This research uses a case studies approach in which data was collected by interviewing a total of twelve e-commerce entrepreneurs from May 2013 until December 2014. The findings of this study have found the contribution to the creation of new businesses by cognitive entrepreneurs in e-commerce in Malaysia is based on personal background (i.e. education, family) and experience in a previous work & business that facilitates their creation of new businesses. Therefore, the government's role in encouraging entrepreneurial activity in the country needs to emphasize elements of entrepreneurs’ cognitive ability in order to enhance the economic development of the country through the emergence of new business in e-commerce in the future